Dynapenia: Term, causes and consequences - Međedović Bojan (University Educons, Faculty of Sports and Tourism, Novi Sad, 2018)
Extended lifespan is one of the greatest achievements of Humanity, but is also accompanied by tremendous challenge. Biological aging is associated with a common process of reducing physical performance, which consequently leads to a decrease of the capacity of the organism. One of the most recognizable consequences of poor physical performance is movement disability. Physical performance is closely related to muscle strength, which decreases with aging. Decrease in muscle strength is a significant health loss contributor and can be a cause of walking mechanics disorders, falls, hip joint fractures and loss of ability to independently perform basic daily activities. It was previously thought that the loss of skeletal muscle mass largely explains muscle weakness commonly observed in older adults. However, recent longitudinal and experimental studies have suggested that muscle atrophy has a relatively small contribution to reduced muscle strength and that other physiological factors independent of tissue size, play an important and, likely, larger role in anticipating individual development of muscle weakness (dynapenia). Reduction in muscle strength with aging is more pronounced than reduction in muscle mass. Resistance training is an effective way for improving strength and size of muscles in healthy adults. It is well-documented that such training positively improves mobility, stability, muscle contraction velocity, magnitude of applied force, etc. However, the guidelines for strength training for adults with significant muscular weakness are not sufficiently precise and detailed. In order to successfully apply such training to people with reduced muscular strength, longitudinal controlled studies are needed with evaluation of biological contributors to muscle weakness, in the context of development an effective program for prevention and treatment of this condition.